2019
DOI: 10.1167/tvst.8.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Myopic Retinal Deformation and Corneal Biomechanical Characteristics Measured With the Corvis ST Tonometry

Abstract: Purpose We previously reported that the retinal deformation due to myopia was represented by the peripapillary retinal arteries angle (PRAA). In this study, we investigated the relationship between the PRAA and biomechanical properties measured with Corvis ST (CST) tonometry. Methods Thirty-four normative eyes of 34 subjects who underwent CST measurement were enrolled. The PRAA was calculated from a fundus photograph. Variables related to the PRAA were identified from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In a meta-analysis of corneal biomechanical properties of 11 related studies using an ocular response analyzer, we found that corneal elasticity decreased significantly in high myopia ( Wu et al, 2019 ). We further showed that corneal stiffness of over 1,000 patients with high myopia provided by Corvis ST also significantly reduced ( Han et al, 2020 ), which is further supported by the findings from other groups ( Zhang et al, 2018 ; Asano et al, 2019 ; Long et al, 2019 ; Kenia et al, 2020 ; Sedaghat et al, 2020 ; Tubtimthong et al, 2020 ). With an experimentally induced myopia model in chicks, the reduction of corneal elasticity and weakness of corneal biomechanics were related to development of myopia ( Kang et al, 2018 ).…”
Section: The Association Of Corneal Diseases With Mechanical Cues In ...supporting
confidence: 86%
“…In a meta-analysis of corneal biomechanical properties of 11 related studies using an ocular response analyzer, we found that corneal elasticity decreased significantly in high myopia ( Wu et al, 2019 ). We further showed that corneal stiffness of over 1,000 patients with high myopia provided by Corvis ST also significantly reduced ( Han et al, 2020 ), which is further supported by the findings from other groups ( Zhang et al, 2018 ; Asano et al, 2019 ; Long et al, 2019 ; Kenia et al, 2020 ; Sedaghat et al, 2020 ; Tubtimthong et al, 2020 ). With an experimentally induced myopia model in chicks, the reduction of corneal elasticity and weakness of corneal biomechanics were related to development of myopia ( Kang et al, 2018 ).…”
Section: The Association Of Corneal Diseases With Mechanical Cues In ...supporting
confidence: 86%
“…We previously reported that a narrow PRAA is related to poor damping capacity of an eye as measured with the Ocular Response Analyzer (Reichert Technologies, Depew, NY, USA) or OCULUS Corvis STL (Oculus, Inc., Menlo Park, CA, USA). 54,55 Such damping capacity of an eye has been reported to be associated with the development and progres-sion of glaucoma and other retinal diseases such as angioid streaks. [56][57][58] We have speculated that eyes are deformed even in daily life activities, such as postural changes, eyelid blinking, ocular pulsatility due to ocular hemodynamics, performing the Valsalva maneuver, and regular eye movement.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the angle between the supratemporal and infratemporal peaks in the profile of the circumpapillary retinal nerve fiber layer RNFL (cpRNFL) narrows with the elongation of an eye, 11 and this is associated with alterations of the biomechanical properties of an eye. 12 14 Indeed, the cpRNFL peak angle can be accurately represented by the angle between supratemporal and infratemporal major retinal arteries (correlation coefficient equal to 0.92). 11 We also reported that correcting the cpRNFL thickness profile using the positions of the major retinal arteries significantly improved the structure-function association between cpRNFL thickness and VF sensitivity.…”
mentioning
confidence: 99%